Documentation of implemented of Nursing process in Jugal Hospital Harar Ethiopia - Jamie, Arif Hussen; Abdosh, Mohammed Zekeria Abdosh (COMMICAST, 2022)
Nursing care documentation has been defined as the record of nursing care that is planned and performed to specific patients and by nurses since the early days of Nightingale. To assess Documentation of Implemented nursing process in Jugal Hospital, Harar, Ethiopia. At Jugal hospital in Harar town, 525 kilometers east of Addis Ababa, hospital-based retrospective study design was used and the research took place from January 1st to 27th,2022.The sample size was derived using the single population proportion calculation, the total sample size was 289. IBM SPSS software package version 20.0 (Armonk, NY: IBM Corp) was used to enter, clean, and analyze data.  The overall the implementation of the nursing process in this study is 62.97 %, With regards to the specific components implemented the result shows that 35.99% charts were recorded with assessment and diagnosis part of the nursing process followed by planning 29.07 % whereas implementation and evaluation parts were the least documented in the hospital. In nursing practice, documentation is important; hence it is believed that what is not recorded has not been done and lack of documentation may make it suspicious that they did not do their duty. So the nursing process committees or the hospital matron and the nurse managers at the hospital should conduct routine supportive supervision on NP.